Head and neck mucosal melanoma: The United Kingdom national guidelines. (October 2020) - Nenclares, Pablo; Ap Dafydd, Derfel; Bagwan, Izhar; Begg, Donna; Kerawala, Cyrus; King, Emma; Lingley, Ken; Paleri, Vinidh; Paterson, Gillian; Payne, Miranda; Silva, Priyamal; Steven, Neil; et al.
Abstract: The United Kingdom head and neck mucosal melanoma guideline development group used an evidence-based systematic approach to make recommendations in key areas of uncertainty in the field, including accurate diagnosis and staging; the appropriate treatment pathway including surgery, adjuvant radiation and new systemic treatments, such as targeted agents and immunotherapy; and the surveillance of patients after treatment. The guidelines were sent for international peer review and have been accredited by the National Institute for Health and Care Excellence. A summary of key recommendations is presented. The full documents are available on the Melanoma Focus website (https://melanomafocus.com/activities/mucosal-guidelines/mucosal-melanoma-resources/ ). Highlights: All head and neck mucosa melanomas are classified as stage III-IV. Prognosis is driven by distant metastases. There is a role of ICI or targeted therapies as adjuvant treatment. Adjuvant RT should be only offered in highly selected patients. Consider entry to clinical trials to all patients.